The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.12659/msm.909059
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Organ Transplantation from Donors with a Cancer History

Abstract: BackgroundThe inherent challenges of selecting an acceptable donor for the increasing number and acuity of recipients has forced programs to take increased risks, including accepting donors with a cancer history (DWCH). Outcomes of organ transplantation using organs from DWCH must be clarified. We assessed transplant outcomes of recipients of organs from DWCH.Material/MethodsRetrospective analysis of the Scientific Registry of Transplant Recipients data from January 1, 2000 to December 31, 2014 identified 8385… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…51−54 Donor malignancy has not been shown to have an increased risk of early death or graft loss overall in solid organ transplant recipients, although hematologic and otolaryngotic tumors have been associated with decreased survival following heart transplant. 55 The Organ Procurement and Transplantation Network has issued a consensus statement on donor malignancy. 56 There are only case reports of genetic syndromes in donors and no conclusions can be drawn.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…51−54 Donor malignancy has not been shown to have an increased risk of early death or graft loss overall in solid organ transplant recipients, although hematologic and otolaryngotic tumors have been associated with decreased survival following heart transplant. 55 The Organ Procurement and Transplantation Network has issued a consensus statement on donor malignancy. 56 There are only case reports of genetic syndromes in donors and no conclusions can be drawn.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Although far less common, donors with active or prior malignancy history are another potential source for organ donation with disease transmission. The largest study assessing this risk evaluated over 8000 potential Chinese donors across all age ranges with a positive cancer history resulting in over 700 organ transplants . While there was no increased incidence of cancer transmission, they found significantly worse survival in heart transplant recipients from donors with either hematologic or otorhinolaryngologic cancers but not with central nervous system tumors.…”
Section: Donor Cause Of Deathmentioning
confidence: 99%
“…While a comprehensive exploration of all other donor comorbidities is not possible in this review, some other pertinent situations were considered. The presence of a donor history of oncologic disease was reviewed as a risk factor for solid organ transplantation using a retrospective review of the Scientific Registry of Transplant Recipients (SRTR) database showed no increased risk of early death or graft loss in recipients of a donor with oncologic history . Although notably, hematologic and otolaryngotic tumors were associated with decreased recipient survival following heart transplantation …”
Section: Donor Comorbiditiesmentioning
confidence: 99%